The role of religious women in the upliftment of the living conditions of urban poor in Iloilo City - Ampil, Vanessa A.; Dalipe, Maeden T.; Duran, Lynde P.; Flores, Gayleen; Geromiano, Mary Mae C. (2002.)
This study dealt with the role of religious women in the upliftment of the lives of Urban Poor in Iloilo City. The study aimed to discover the role that religious women play in the society, particularly in the upliftment of the urban poor. It also dealt with the ways that these religious women employ to help improve the living conditions of the poor. This study covered eleven women religious orders and 150 of their beneficiaries. Interviews and questionnaires were utilized in the data-gathering phase. After a series of data gathering and analysis, it was determined that religious women play an important part in uplifting the lives of urban poor by implementing various programs and projects. These include livelihood projects, outreach programs, educational assistance program, medical assistance program, loan cooperatives, trainings and seminars. Based on the group's analysis and evaluation, these programs and projects in a way helped improve the living conditions of urban poor.
Research Paper (BA 200 - Business Paper) -- Iloilo City : University of the Philippines in the Visayas-College of Management, April 2002.